PENERAPAN MODEL PEMBELAJARAN INKUIRI DENGANPENDEKATAN SAVI ( SOMATIC, AUDITORY, VISUAL, ANDINTELLECTUAL) UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA PADA SUB POKOK BAHASAN LUAS PERMUKAAN DAN VOLUME BANGUN RUANG SISI LENGKUNG DI SMPN 2 JENGGAWAHK - Triani, Zunita Khuna; Hobri, H; Setiawan, Toto' Bara (Kadikma, 2013)
Abstract.Inquiry is the learning model that emphasis oncritical thinkingand analyticalprocesstofind their ownanswers toaproblem,andSAVIis a combinationof physical movementand intellectualactivity. The aims of this research is to know implementation of inquiry learning model with SAVI approach to increase students mathematic outcome and student’s activity for the students of class IX. Type of research is Classroom Action Research (CAR) and the study design used was a model scheme Kemmis dan Taggartstudy research design were consists of 4 phases include planning, action, observation, and reflection. Thesubject of the research isIX C students of SMP Negeri 2 Jenggawah and material was chosen surface area and volume of curved space geometry. The data collection methods used in this research was observation, interview, test, and documentation.In the first cycle, completeness student’s activity is 77,05% and the student learning outcomes classically is 72,22%. And the second cycle, completeness the student’s activity is 86,57% and the student learning outcomes classically is 86,11%. So the increase of the both cycle classically above was 13,89%. The result shows that the completeness of student’s activity and result learning has increased well. Keywords: Inkuiri Learning Model, SAVI approach,Surface Area And Volume Of Curved Space Geometry,Student’s result study.